Modeling the Impact of Attachment Styles on Work Ethics with the Mediating Role of Job Adaptability - Sadeqh, Hossein; Khakpour, Reza; Shafiabadi , Abdollah (Mental Health and Lifestyle Journal, 2024)
The objective of this study was to model the impact of attachment styles on work ethics among judicial employees, examining the mediating role of job adaptability in this relationship. This research employed a quantitative, correlational design using path analysis within the framework of structural equation modeling (SEM). The statistical population consisted of employees from the central headquarters of the Judiciary of the Islamic Republic of Iran and the Judiciary Research Institute in Tehran. A total of 108 participants were selected using convenience sampling. Data were collected through validated instruments, including the Hazan and Shaver Attachment Style Questionnaire, Petty’s Work Ethics Questionnaire, and the Davis and Lofquist Job Adaptability Scale. Descriptive and inferential statistics were conducted using SPSS and LISREL software. The results indicated that secure attachment style had a significant positive direct effect on both job adaptability (β = 0.33, t = 4.50) and work ethics (β = 0.39, t = 5.27). Moreover, job adaptability partially mediated the relationship between secure attachment and work ethics, with an indirect effect of 0.13 and a total effect of 0.52. In contrast, avoidant and anxious-ambivalent attachment styles did not show significant effects on either job adaptability or work ethics. Model fit indices (χ²/df = 2.34, GFI = 0.95, AGFI = 0.91, RMSEA = 0.078) confirmed a good fit between the proposed conceptual model and the data. These findings suggest that secure attachment plays a critical role in promoting ethical behavior in professional contexts, both directly and through enhanced adaptability. Organizations aiming to foster ethical work environments should consider psychological factors such as attachment styles and invest in training programs that support adaptability and emotional regulation.